Maladaptive Cognitive Schemes for Orphans and Non-Orphans Secondary School Students - AL-Abbasi, Rana Abdul-Mun’em; Abd Farhan, Abbas Raheem (Al-Adab Journal, 2021)
maladaptive cognitive traits that are considered as molds that treat or process an individual’s new experiments or information as well as previous memories which form (together) the corner stone for building and shaping personality. The schemes involve stable and consistent forms that tend to develop through a child’s relationships with others, and the painful and hard experiences affecting his own environment. Thus, such schemes become a collection of past experiences that develop to beliefs and traditions in which a person see himself in addition to his environment, in addition to the others surrounding him. Based on the abovementioned argument, the present study is concerned with orphans and non-orphan secondary students, owing to the fact that childhood experiences and parental role in a child’s growing have a great impact in forming the cognitive schemes. The current study aims at the following: Identifying the sense of private self for orphans and non-orphan’s secondary students.